Implementation fidelity of a computer-assisted intervention for children with speech sound disorders. (4th May 2017) - McCormack, Jane; Baker, Elise; Masso, Sarah; Crowe, Kathryn; McLeod, Sharynne; Wren, Yvonne; Roulstone, Sue
Abstract: Background : Implementation fidelity refers to the degree to which an intervention or programme adheres to its original design. This paper examines implementation fidelity in the Sound Start Study, a clustered randomised controlled trial of computer-assisted support for children with speech sound disorders (SSD). Method : Sixty-three children with SSD in 19 early childhood centres received computer-assisted support (Phoneme Factory Sound Sorter [PFSS] – Australian version). Educators facilitated the delivery of PFSS targeting phonological error patterns identified by a speech-language pathologist. Implementation data were gathered via (1) the computer software, which recorded when and how much intervention was completed over 9 weeks; (2) educators' records of practice sessions; and (3) scoring of fidelity (intervention procedure, competence and quality of delivery) from videos of intervention sessions. Result : Less than one-third of children received the prescribed number of days of intervention, while approximately one-half participated in the prescribed number of intervention plays. Computer data differed from educators' data for total number of days and plays in which children participated; the degree of match was lower as data became more specific. Fidelity to intervention procedures, competency and quality of delivery was high. Conclusion : Implementation fidelity may impact intervention outcomes and so needs to be measured in intervention research; however, the way in which it is measured may impact on data.